Modeling the economic and health impact of substandard uterotonics in Senegal - Yi-Fang Ashley Lee; Colleen R. Higgins; Petra Procter; Sara Rushwan; A. Metin Gülmezoglu; Lester Chinery; Sachiko Ozawa (BMC Pregnancy and Childbirth)
Abstract Background Maternal mortality due to postpartum hemorrhage (PPH) remains a global concern especially in low- and lower-middle income countries. PPH is preventable with quality-assured uterotonics. However, substandard uterotonics pose a significant risk to PPH, and there is limited evidence available to provide quantitative estimates of their economic impact. This study aims to evaluate the impact of ensuring uterotonic quality in Senegal, highlighting the potential to lower healthcare costs, reduce maternal deaths, and contribute to achieving Sustainable Development Goals related to maternal health and Universal Healthcare Coverage. Methods We utilized a decision tree model to estimate the economic and health impact of improving the quality of uterotonics in prevention of PPH in Senegal. We simulated women giving birth in various healthcare settings, receiving uterotonics of varied quality, and subsequent PPH-related outcomes. Data from the Senegal Demographic and Health Survey, Cochrane review, and E-MOTIVE trial informed the model. We compared scenarios with and without substandard uterotonics, along with scenarios altering uterotonic usage and care-seeking behavior. Results Our findings indicate that utilizing quality-assured uterotonics in Senegal could lead to a notable 7–9% reduction in the overall economic burden of PPH, saving over 1 million USD annually in direct costs and long-term productivity losses. Improving the quality of uterotonics in Senegal would result in a 6–8% reduction in PPH cases, translating to over 5,000 fewer PPH cases annually. Using quality uterotonics instead of substandard ones also decreased deaths from PPH by 6–8% annually. Conclusions This study underscores the importance of ensuring uterotonic quality to showcase significant cost savings and improvements in maternal health outcomes in Senegal. The accrued cost savings from improved maternal health outcomes related to PPH prevention and treatment would greatly benefit mothers, their families, healthcare providers, and the healthcare system. This case study offers valuable insights into improving the quality of maternal care and achieving more efficient resource allocation to advance Senegal’s progress towards Universal Health Coverage.